Community actions for the social management of environmental knowledge in the Edecio Pérez community in the municipality of Holguín - Varona Domínguez, Ricardo Daniel (Revista General de Información y Documentación, 2018)
The growing degradation of the environment is a phenomenon that has occupied and preoccupied society since the middle of the last century. These problems are of indisputable importance in the contemporary world in the face of aggravation of ecological affectations. These are the challenges of the present century and the impact of society as a modifier of both natural and built environments. This research is aimed at enhancing the perception of the environment in community contexts from a science, technology and society approach, valid to visualize science as a factor of change in different scenarios. The question is how to socially manage environmental knowledge in the community "Edecio Pérez" of the municipality of Holguin? Based on this problem, a set of actions is proposed for the social management of environmental knowledge that can favor the participatory awareness of its inhabitants for the solution of the problems that affect the development of society. This premise aims to raise awareness, environmental awareness of the inhabitants, from their own potential. To develop in the individual a critical awareness of the need to change the state of affairs in the environmental order and as a valid tool to mobilize society in order to raise their quality of life. Various community activities have been developed, fundamentally as part of the Life Task, it must work in an integrated manner to reduce pollution levels, recover biodiversity, soils and watersheds. The implementation of the State Plan for confronting climate change, Task Life, is a priority and has a positive impact on the protection of the environment.